Co-Design for Rebranding an Italian Foundation - Xue Pei; Francesco Zurlo (Agathón)
This paper is based on research conducted by Creative Industries Lab of Politecnico di Milano for creating the new brand image and communication strategy for Fondazione Cariplo. A Co-Design approach has involved both internal and external stakeholders in visually defining a shared future identity for rebranding this significant foundation to the public. The research results have revealed that the co-creation process has not only generated the expected objectives, but also raised a cultural change towards innovation inside the organization itself. Therefore, this experience has opened a new research realm for applying design methods and tools in organizations.